The role of creativity in expertise and skilled action. - Ivy, Spencer (Synthese, 2022)
Perhaps a part of what makes expertise so inspiring to the curious researcher is the possibility of appropriating the structural components of skilled action to draw a roadmap towards their achievement that anyone might be able to follow. Accordingly, the purpose of this essay is to shed light upon the role that creativity plays in the production and environment of skilled action to that foregoing end. In doing so, I suggest that the lessons to be learned from recent empirical research on creativity has much to offer to the cognitive science of skill and expertise. Experts are able to bring their intelligence to bear in controlling fast and seemingly automatic actions by utilizing a form of control often called ‘intelligent automaticity.’ In this spirit, I argue that the environment of intelligently automatic action control curates a similarly ideal environment for the processes of creativity. Moreover, insofar as creativity is ideally operative within the environment of expert action control, I argue further that creativity functions as one representative form of ‘intelligence’ embedded within otherwise fluid, and automatic expert actions. Creativity is able to do so even without conscious representation through the powers of incubated cognition.